Zizyphus lotus (L.) extracts as prebiotics in the aggregation and adhesion of probiotic and inhibition of pathologic bacteria from patients with colorectal cancer - Sara Ouldchikh; Aicha TirTouil; Boumédiene Meddah (International Journal of Food Studies)
The mucosal surfaces of the intestinal tract harbor a complex microbiota. Bacteria enter in contact with intestinal cells and bestow important nutritional, metabolic and protective functions which benefit the host. Various factors are able to alter the balances between different intestinal bacteria. Dysbiosis has been described in various pathologies and metabolic diseases in humans, such as cancer. Colorectal cancer pathology can benefit from gut microbial imbalance. Its overgrowth may lead to acute symptoms. An alternative strategy to restore this balance is the use of plant extracts which exhibit a prebiotic activity by stimulating of probiotic bacteria and antimicrobial activity against pathogenic bacteria colonization. The present study aims to evaluate the in vitro antioxidant and antibacterial activity of phenolic extracts (Aqueous extract "AE" and Methanolic extract "ME" ) from Zizyphus lotus. It aims also to investigate the effect of this extract as a prebiotic on the aggregation of probiotic and inhibitory effects of pathogenic bacteria isolated from faeces of patients with colorectal cancer. Phytochemical analysis of different extracts from Zizyphus lotus by HPLC showed that all are rich in phenolic compounds (225.40 mgAGE/gDW for AE and 63.04 mgAGE/gDW for ME extracts). Moreover, all extracts showed an important antioxidant activity (227 µg/ml for AE and 195 µg/ml for ME). These extracts also exhibited a significant prebiotic effect and antibacterial activity. Characterization of the in vitro effect of the aqueous extract showed that the percentage of autoaggregation and adhesion of probiotic and inhibitory effects of pathogenic bacteria increased in the presence of aqueous extracts.